Internal Management Systems and Supply Chain Relationship Commitment in State-Owned Enterprise in Gauteng Province - Pfanelo Nematatani; Elizabeth Chinomona (African Journal of Inter-Multidisciplinary Studies)
Internal management systems (IMS) are a set of techniques that drive enterprises to remain competitive throughout their existence. For state-owned enterprises (SOEs) to discover their constraints, the impact of IMS on supply chain relationship commitment must be investigated. The paper aims to examine the influence of IMS on supply chain relationship commitment in SOEs in Gauteng Province. A quantitative method was adopted for the study and a questionnaire was distributed physically and electronically to 863 respondents drawn from SOEs in Gauteng Province. Information was analysed through two software packages, namely SPSS (version 27.0) and Smart PLS 3.0. A confirmatory factor analysis was applied in examining and testing the relationships between innovation, knowledge management, behaviour integration, total quality management, safety management on supply chain relationship commitment and their causal latent constructs while structural equation modelling helped in testing the hypothesised relationships among variables. The investigation concludes that to achieve efficient supply chain relationship commitments, SOEs should examine the levels of innovation, knowledge management, behaviour integration, total quality management and safety management.